Absolute quantification of DcR3 and GDF15 from human serum by LC-ESI MS - Lancrajan, Ioana Maria; Schneider-Stock, Regine; Naschberger, Elisabeth; Schellerer, Vera; Stürzl, Michael; Enz, Ralf (Journal of Cellular and Molecular Medicine, 2015)
Biomarkers are widely used in clinical diagnosis, prognosis and therapy monitoring. Here, we developed a protocol for the efficient and selective enrichment of small and low concentrated biomarkers from human serum, involving a 95% effective depletion of high-abundant serum proteins by partial denaturation and enrichment of low-abundant biomarkers by size exclusion chromatography. The recovery of low-abundance biomarkers was above 97%. Using this protocol, we quantified the tumour markers DcR3 and growth/differentiation factor (GDF)15 from 100 ?l human serum by isotope dilution mass spectrometry, using (15) N metabolically labelled and concatamerized fingerprint peptides for the both proteins. Analysis of three different fingerprint peptides for each protein by liquid chromatography electrospray ionization mass spectrometry resulted in comparable concentrations in three healthy human serum samples (DcR3: 27.23 ± 2.49 fmol/ml; GDF15: 98.11 ± 0.49 fmol/ml). In contrast, serum levels were significantly elevated in tumour patients for DcR3 (116.94 ± 57.37 fmol/ml) and GDF15 (164.44 ± 79.31 fmol/ml). Obtained data were in good agreement with ELISA and qPCR measurements, as well as with literature data. In summary, our protocol allows the reliable quantification of biomarkers, shows a higher resolution at low biomarker concentrations than antibody-based strategies, and offers the possibility of multiplexing. Our proof-of-principle studies in patient sera encourage the future analysis of the prognostic value of DcR3 and GDF15 for colon cancer patients in larger patient cohorts.
EVALuna2:4708

A proline-rich motif in the large intracellular loop of the glycine receptor α1 subunit interacts with the Pleckstrin homology domain of collybistin - Breitinger, Ulrike; Weinländer, Kristina; Pechmann, Yvonne; Langlhofer, Georg; Enz, Ralf; Becker, Cord-Michael; Sticht, Heinrich; Kneussel, Matthias; Villmann, Carmen; Breitinger, Hans Georg (Journal of Advanced Research, 2020)
Introduction: The inhibitory glycine receptor (GlyR), a mediator of fast synaptic inhibition, is located and held at neuronal synapses through the anchoring proteins gephyrin and collybistin. Stable localization of neurotransmitter receptors is essential for synaptic function. In case of GlyRs, only beta subunits were known until now to mediate synaptic anchoring. Objectives: We identified a poly-proline II helix (PPII) in position 365–373 of the intra-cellular TM3-4 loop of the human GlyRα1 subunit as a novel potential synaptic anchoring site. The potential role of the PPII helix as synaptic anchoring site was tested. Methods: Glycine receptors and collybistin variants were generated and recombinantly expressed in HEK293 cells and cultured neurons. Receptor function was assessed using patch-clamp electrophysiology, protein-protein interaction was studied using co-immuno-precipitation and pulldown experiments. Results: Recombinantly expressed collybistin bound to isolated GlyRα1 TM3-4 loops in GST-pulldown assays. When the five proline residues P365A, P366A, P367A, P369A, P373A (GlyRα1P1-5A) located in the GlyRα1-PPII helix were replaced by alanines, the PPII secondary structure was disrupted. Recombinant GlyRα1P1-5A mutant subunits displayed normal cell surface expression and wildtype-like ion channel function, but binding to collybistin was abolished. The GlyRα1-collybistin interaction was independently confirmed by o-immunoprecipitation assays using full-length GlyRα1 subunits. Surprisingly, the interaction was not mediated by the SH3 domain of collybistin, but by its Pleckstrin homology (PH) domain. The mutation GlyRα1P366L, identified in a hyperekplexia patient, is also disrupting the PPII helix, and caused reduced collybistin binding. Conclusion: Our data suggest a novel interaction between α1 GlyR subunits and collybistin, which is physiologically relevant in vitro and in vivo and may contribute to postsynaptic anchoring of glycine receptors.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Collybistin; Gephyrin; Glycine receptor alpha1 subunit; Ion channel receptors; Pleckstrin homology domains; Polyproline II helix; Protein-protein interaction; SH3 domains; Synaptic anchoring

A single point mutation decreases picrotoxinin sensitivity of the human GABA receptor *1 subunit. - Enz, Ralf (NeuroReport, 1995)
UnivIS-Import:2017-12-18:Pub.1995.med.IB.profes_1.asingl

Band 4.1 proteins are expressed in the retina and interact with both isoforms of the metabotropic glutamate receptor type 8. - Rose, Melanie; Dütting, E.; Enz, Ralf (Journal of Neurochemistry, 2008)
The function of the CNS depends on the correct regulation of neurotransmitter receptors by interacting proteins. Here, we screened a retinal cDNA library for proteins interacting with the intracellular C-terminus of the metabotropic glutamate receptor isoform 8a (mGluR8a). The band 4.1B protein binds to the C-termini of mGluR8a and mGluR8b, co-localizes with these glutamate receptors in transfected mammalian cells, facilitates their cell surface expression and inhibits the mGluR8 mediated reduction of intracellular cAMP concentrations. In contrast, no interaction with 4.1B was observed for other mGluRs tested. Amino acids encoded by exons 19 and 20 of 4.1B and a stretch of four basic amino acids present in the mGluR8 C-termini mediate the protein interaction. Besides binding to 4.1B, mGluR8 isoforms interact with 4.1G, 4.1N, and 4.1R. Because band 4.1 transcripts undergo extensive alternative splicing, we analyzed the splicing pattern of interacting regions and detected a 4.1B isoform expressed specifically in the retina. Within this tissue, mGluR8 and 4.1B, 4.1G, 4.1N, and 4.1R show a comparable distribution, being expressed in both synaptic layers and in somata of the ganglion cell layer. In summary, our studies identified band 4.1 proteins as new players for the mGluR8 mediated signal transduction. © 2008 The Authors.
UnivIS-Import:2017-12-18:Pub.2008.med.IB.profes_1.band41
Keywords: Alternative splicing; Protein interaction; Retina; Synaptic signal complex

Binding partners of metabotropic glutamate receptors. - Enz, Ralf (Molecular aspects of G protein-coupled receptors: Interacting proteins and function, 2008)
UnivIS-Import:2017-12-18:Pub.2008.med.IB.profes_1.bindin

Cereblon is expressed in the retina and binds to voltage-gated chloride channels. - Hohberger, Bettina; Enz, Ralf (FEBS letters, 2009)
UnivIS-Import:2018-09-11:Pub.2009.med.IB.profes_1.cerebl
Keywords: Cereblon; CIC-1; CIC-2; CRBN; Protein interaction; Retina

CRIP1a inhibits endocytosis of G-protein coupled receptors activated by endocannabinoids and glutamate by a common molecular mechanism - Mascia, Fabrizio; Klotz, Lisa; Lerch, Judith; Ahmed, Mostafa H.; Zhang, Yan; Enz, Ralf (Journal of Neurochemistry, 2017)
The excitability of the central nervous system depends largely on the surface density of neurotransmitter receptors. The endocannabinoid receptor 1 (CB1 R) and the metabotropic glutamate receptor mGlu8 R are expressed pre-synaptically where they reduce glutamate release into the synaptic cleft. Recently, the CB1 R interacting protein cannabinoid receptor interacting protein 1a (CRIP1a) was identified and characterized to regulate CB1 R activity in neurons. However, underlying molecular mechanisms are largely unknown. Here, we identified a common mechanism used by CRIP1a to regulate the cell surface density of two different types of G-protein coupled receptors, CB1 R and mGlu8a R. Five amino acids within the CB1 R C-terminus were required and sufficient to reduce constitutive CB1 R endocytosis by about 72% in the presence of CRIP1a. Interestingly, a similar sequence is present in mGlu8a R and consistently, endocytosis of mGlu8a R depended on CRIP1a, as well. Docking analysis and molecular dynamics simulations identified a conserved serine in CB1 R (S468) and mGlu8a R (S894) that forms a hydrogen bond with the peptide backbone of CRIP1a at position R82. In contrast to mGlu8a R, the closely related mGlu8b R splice-variant carries a lysine (K894) at this position, and indeed, mGlu8b R endocytosis was not affected by CRIP1a. Chimeric constructs between CB1 R, mGlu8a R, and mGlu8b R underline the role of the identified five CRIP1a sensitive amino acids. In summary, we suggest that CRIP1a negatively regulates endocytosis of two different G-protein coupled receptor types, CB1 R and mGlu8a R.
EVALuna2:4771

Different binding domains in the metabotropic glutamat receptor type 7b for Filamin-A, PP1C, PICK1 and Syntenin allow the formation of multimeric protein complexes. - Enz, Ralf; et al. (Biochemical Journal, 2003)
UnivIS-Import:2017-12-18:Pub.2003.med.IB.profes_1.differ

Endocytosis of GABA(C) receptors depends on subunit composition and is regulated by protein kinase C-? and protein phosphatase 1 - Linck, Lisa; Binder, Jasmin; Haynl, Christian; Enz, Ralf (Journal of Neurochemistry, 2015)
Neuronal excitability depends on the surface concentration of neurotransmitter receptors. Type C gamma-aminobutyric acid receptors (GABA(C)R) are composed of ? subunits that are highly expressed in the retina. Molecular mechanisms that guide the surface concentration of this receptor type are largely unknown. Previously, we reported physical interactions of GABA(C)R ? subunits with protein kinase C-? (PKC?) via adapter proteins of the ZIP protein family, as well as of protein phosphatase 1 (PP1) via PNUTS. Here, we demonstrate that co-expressing ?1 with ZIP3 and PKC? enhanced basal internalization of GABA(C)R, while receptor internalization was reduced in the presence of PNUTS and PP1. Co-expression of ?1 with individual binding partners showed no alterations, except for PP1. Heterooligomeric GABA(C)R composed of ?1 and ?2 subunits had a significant higher endocytosis rate than ?1 containing homooligomeric receptors. Mutant constructs lacking binding sites for protein interactions ensured the specificity of our data. Finally, substitution of serine and threonine residues with alanines indicated that GABA(C)R internalization depends on serine/threonine kinases and phosphatases, but not on tyrosine phosphorylation. We conclude that GABA(C)R internalization is reciprocally regulated by PKC? and PP1 that are anchored to the receptor via ZIP3 or PNUTS respectively.
EVALuna2:4723

Expression of the mRNA of seven metabotropic glutamate receptors (mGluR1 to 7) in the rat retina. An in situ hybridization study on tissue sections and isolated cells. - Enz, Ralf; et al. (European Journal of Neuroscience, 1995)
UnivIS-Import:2017-12-18:Pub.1995.med.IB.profes_1.expres_65
Keywords: glutamate; hybridization; in situ; metabotropic receptors; oligonucleotide probes

Expression of the voltage-gated chloride channel ClC-2 in rod bipolar cells of the rat retina. - Enz, Ralf; et al. (Journal of Neuroscience, 1999)
Voltage-gated chloride channels (ClC) are highly conserved during evolution and appear to participate in a variety of physiological functions. Recently, ClC-2 was proposed to play a role in stabilizing the chloride equilibrium potential near or below the resting membrane potential in neurons expressing ligand-gated chloride channels. Because rod bipolar cells in mammalian retina express three forms of inhibitory ligand-gated chloride channels, we decided to study ClC-2 localization and function in the rat retina. RNA encoding ClC-1, -2, -3, -4, and -5 was detected by reverse transcription-PCR in the rat retina. ClC-2-specific antibodies identified protein on cell bodies and in synaptic layers. Double-immunofluorescence staining revealed that intense ClC-2 immunoreactivity colocalized with PKC- stained rod bipolar cells. Patch-clamp experiments performed with individual rod bipolar cells demonstrated the presence of a time-dependent, inwardly rectified current activated at hyperpolarizing membrane potentials. This current demonstrated selectivity for different anions (Cl- > l- > gluconate), was inhibited by Cd2+, and was minimally reduced by 4,4'- diisothiocyanatostilbene-2,2'-disulphonic acid. These features are consistent with currents generated by ClC-2 channels. Our data indicate that functional ClC-2 channels are present in retinal rod bipolar cells and support a role for ClC-2 in maintaining Cl- homeostasis in neurons with ligand-gated chloride channels.
UnivIS-Import:2017-12-18:Pub.1999.med.IB.profes_1.expres
Keywords: ClC; CNS; GABA receptor; Ligand-gated ion channel; Retina; Rod bipolar cell; Voltage-gated chloride channel

Expression, purification, and structural analysis of intracellular C-termini from metabotropic glutamate receptors - Seebahn, Angela; Sticht, Heinrich; Enz, Ralf (Methods in Enzymology, 2013)
Glutamate is the most important excitatory neurotransmitter in the mammalian central nervous system (CNS). Metabotropic glutamate receptors (mGluRs) are G-protein-coupled receptors (GPCRs) that guide several intracellular signal cascades thereby controlling multiple physiological tasks, such as neuronal excitability, learning, and memory. Consequently, these receptors are discussed in the context of several CNS-associated diseases, including addiction for drugs, Alzheimer's disease, Fragile X syndrome, night blindness, or schizophrenia. Although increasing structural information is available for the extracellular and transmembrane domains of GPCRs, data describing the nature of intracellular receptor domains are largely missing. Indeed, in all available crystal structures of neurotransmitter receptors, their intracellular domains were omitted. Most intracellular mGluR C-termini are alternatively spliced and contain multiple binding sites for interacting proteins. Therefore, analyzing their structure can identify molecular mechanisms of receptor regulation. Recently, we analyzed the conformation of the intracellular C-termini of mGluR6, mGluR7a, and mGluR8a. Here, we describe an array of biochemical, biophysical, and computational techniques suited to elucidate the nature of these highly interesting receptor domains.
EVALuna2:4686

GABAC Receptors: A Molecular View. - Enz, Ralf (Biological Chemistry, 2001)
In the central nervous system inhibitory neurotransmission is primarily achieved through activation of receptors for γ-aminobutyric acid (GABA). Three types of GABA receptors have been identified on the basis of their pharmacological and electrophysiological properties. The predominant type, termed GABAA, and a recently identified GABAC type, form ligand-gated chloride channels, whereas GABAB receptors activate separate cation channels via G proteins. Based on their homology to nicotinic acetylcholine receptors, GABAC receptors are believed to be oligomeric protein complexes composed of five subunits in a pentameric arrangement. To date up to five different GABAC receptors subunits have been identified in various species. Recent studies have shed new light on the biological characteristics of GABAC receptors, including the chromosomal localization of its subunit genes and resulting links to deseases, the cloning of new splice variants, the identification of GABAC receptor-associated proteins, the identification of domains involved in subunit assembly, and finally structure/function studies examining functional consequences of introduced mutations. This review summarizes recent data in view of the molecular structure of GABAC receptors and presents new insights into the biological function of this protein in the retina.
UnivIS-Import:2017-12-18:Pub.2001.med.IB.profes_1.gabacr
Keywords: Inhibition; Ligand-gated ion channel; Retina; Rho subunit; Splice variant; Subunit assembly

GABA receptor rho subunit expression in the developing rat brain. - Enz, Ralf; et al. (DEV BRAIN RES, 2005)
Ionotropic GABA C receptors are composed of ρ 1, ρ 2 and ρ 3 subunits. Although the distribution of ρ subunit mRNAs in the adult brain has been studied, information on the developmental regulation of different ρ subunits in the brain is scattered and incomplete. Here, GABA C receptor ρ subunit expression was studied in the developing rat brain. In situ hybridization on postnatal brain slices showed ρ 2 mRNA expression from newborn in superficial gray layer (SGL) of superior colliculus (SuC), and from the first postnatal week in the hippocampal CA1 region and pretectal nucleus of the optic tract. ρ 2 mRNA was also expressed in the adult dorsal lateral geniculate nucleus. Quantitative RT-PCR revealed expression of all three ρ subunits in the hippocampus and superior colliculus from the first postnatal day. In the hippocampus, ρ 2 mRNA expression clearly dominated over ρ 1 and ρ 3, whereas in the superior colliculus, ρ 1 mRNA expression levels were similar to ρ 2. In both areas, a clear up-modulation of ρ 2 and ρ 3 mRNA during the first postnatal week was detected. GABA C receptor protein expression was confirmed in adult hippocampus, superior colliculus and dorsal lateral geniculate nucleus by immunohistochemistry. Our results demonstrate for the first time the expression of all three ρ subunit mRNAs in several regions of the developing and adult rat brain. Our quantitative data allows assessment of putative subunit combinations in the superior colliculus and hippocampus. From the selective distribution of ρ subunits, it may be hypothesized that GABA C receptors are specifically involved in aspects of visual image motion processing in the rat brain. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2017-12-18:Pub.2005.med.IB.profes_1.gabare
Keywords: GABA; Hippocampus; Immunohistochemistry; In situ hybridization; qRT-PCR; Superior colliculus

Group I metabotropic glutamate receptors bind to protein phosphatase 1C: Mapping and modeling of interacting sequences. - Croci, Cristina; Sticht, Heinrich; Brandstätter, Johann Helmut; Enz, Ralf (Journal of Biological Chemistry, 2003)
The modulation of neurotransmitter receptors by kinases and phosphatases represents a key mechanism in controlling synaptic signal transduction. However, molecular determinants involved in the specific targeting and interactions of these enzymes are largely unknown. Here, we identified both catalytic γ-isoforms of protein phosphatase 1C (PP1γ1 and PP1γ2) as binding partners of the group I metabotropic glutamate receptors type 1a, 5a, and 5b in yeast cells and pull-down assays, using recombinant and native protein preparations. The tissue distribution of interacting proteins was compared, and protein phosphatase 1C was detected in dendrites of retinal bipolar cells expressing the respective interacting glutamate receptors. We mapped interacting domains within binding partners and identified five amino acids in the intracellular C termini of the metabotropic glutamate receptors type 1a, 5a, 5b, and 7b being both necessary and sufficient to bind protein phosphatase 1C. Furthermore, we show a dose-dependent competition of these C termini in binding the enzyme. Based on our data, we investigated the structure of the identified amino acids bound to protein phosphatase 1C by homology-based molecular modeling. In summary, these results provide a molecular description of the interaction between protein phosphatase 1C and metabotropic glutamate receptors and thereby increase our understanding of glutamatergic signal transduction.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.profes_1.groupi

Homodimerization of a proximal region within the C-terminus of the orphan G-protein coupled receptor GPR179 - Bachert, Wolfrat; Klotz, Lisa; Sticht, Heinrich; Enz, Ralf (Neurochemistry International, 2021)
G-protein coupled receptors exhibit numerous biological functions. The orphan G-protein coupled receptor GPR179 is a central component of a 1 Megadalton large signalling complex in the ON-pathway of the mammalian retina that assembles multiple proteins, including the metabotropic glutamate receptor mGluR6. Dimer formation is a hallmark of G-protein coupled receptors and some use intracellular C-termini for dimerization. Here we tested the dimerization properties of the intracellular C-terminal domains of mGluR6 and GPR179. While the C-termini of GPR179 and mGluR6 did not interact, we detected a robust homodimerization of a proximal region in the GPR179 C-terminus. Mapping studies defined a linear stretch of 64 amino acids as dimerization region. Bioinformatic analysis indicated that this dimerization region might adopt an α-helical structure that is predicted to dimerize by forming a coiled-coil. Based on these data, we speculate that homodimerization of GPR179 might contribute to the formation of large signalling complexes in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-13
Keywords: C-terminus; Coiled-coil; GPR179; mGluR6; Protein-protein interaction; Retina

Identification and characterisation of Simiate, a novel protein linked to the fragile X syndrome - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (PLoS ONE, 2013)
A strict regulation of protein expression during developmental stages and in response to environmental signals is essential to every cell and organism. Recent research has shown that the mammalian brain is particularly sensitive to alterations in expression patterns of specific proteins and cognitive deficits as well as autistic behaviours have been linked to dysregulated protein expression. An intellectual disability characterised by changes in the expression of a variety of proteins is the fragile X syndrome. Due to the loss of a single mRNA binding protein, the Fragile X Mental Retardation Protein FMRP, vast misregulation of the mRNA metabolism is taking place in the disease. Here, we present the identification and characterisation of a novel protein named Simiate, whose mRNA contains several FMRP recognition motifs and associates with FMRP upon co-precipitation. Sequence analysis revealed that the protein evolved app. 1.7 billion years ago when eukaryotes developed. Applying antibodies generated against Simiate, the protein is detected in a variety of tissues, including the mammalian brain. On the subcellular level, Simiate localises to somata and nuclear speckles. We show that Simiate and nuclear speckles experience specific alterations in FMR1(-/-) mice. An antibody-based block of endogenous Simiate revealed that the protein is essential for cell survival. These findings suggest not only an important role for Simiate in gene transcription and/or RNA splicing, but also provide evidence for a function of nuclear speckles in the fragile X syndrome. Indeed, transcription and splicing are two fundamental mechanisms to control protein expression, that underlie not only synaptic plasticity and memory formation, but are also affected in several diseases associated with mental disabilities.
EVALuna2:4700

Identification of 70 amino acids important for GABAC receptor  subunit assembly. - Enz, Ralf; Cutting (Brain Research, 1999)
UnivIS-Import:2017-12-18:Pub.1999.med.IB.profes_1.identi

Identification of developmentally regulated expression of MuSK in astrocytes of the rodent retina. - Cheusova, Tatiana; Khan, Muhammad Amir; Enz, Ralf; Hashemolhosseini, Said (Journal of Neurochemistry, 2006)
One of the master regulators of postsynaptic neuromuscular synaptogenesis is the muscle-specific receptor tyrosine kinase (MuSK). In mammals prominent MuSK expression is believed to be restricted to skeletal muscle. Upon activation by nerve-derived agrin MuSK-dependent signalling participates in both the induction of genes encoding postsynaptic components and aggregation of nicotinic acetylcholine receptors (AChR) in the subsynaptic muscle membrane. Strikingly, expression of certain isoforms of nerve-derived agrin can also be detected in the CNS. In this study, we examined the expression of MuSK in the brain and eye of rodents. In the retina MuSK was expressed in astrocytes between postnatal days 7 and 14, i.e. at the time when the eyes open. We found that agrin was localized adjacent to MuSK-expressing astrocytes which in turn were detected close to the inner limiting membrane of the rodent retina. In summary, the presence of MuSK on retinal astrocytes suggests a novel role of MuSK signalling pathways in the CNS. © 2006 The Authors.
UnivIS-Import:2015-04-14:Pub.2006.med.IB.LPCIPDBI.identi
Keywords: Agrin; Astrocytes; Eye; Muscle-specific receptor tyrosine kinase; Neuromuscular junction; Retina

Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses - Klotz, Lisa; Wendler, Olaf; Frischknecht, Renato; Shigemoto, Ryuichi; Schulze, Holger; Enz, Ralf (The FASEB Journal, 2019)
Glutamate is the major excitatory neurotransmitter in the CNS binding to a variety of glutamate receptors. Metabotropic glutamate receptors (mGluR1 to mGluR8) can act excitatory or inhibitory, depending on associated signal cascades. Expression and localization of inhibitory acting mGluRs at inner hair cells (IHCs) in the cochlea are largely unknown. Here, we analyzed expression of mGluR2, mGluR3, mGluR4, mGluR6, mGluR7, and mGluR8 and investigated their localization with respect to the presynaptic ribbon of IHC synapses. We detected transcripts for mGluR2, mGluR3, and mGluR4 as well as for mGluR7a, mGluR7b, mGluR8a, and mGluR8b splice variants. Using receptor-specific antibodies in cochlear wholemounts, we found expression of mGluR2, mGluR4, and mGluR8b close to presynaptic ribbons. Super resolution and confocal microscopy in combination with 3-dimensional reconstructions indicated a postsynaptic localization of mGluR2 that overlaps with postsynaptic density protein 95 on dendrites of afferent type I spiral ganglion neurons. In contrast, mGluR4 and mGluR8b were expressed at the presynapse close to IHC ribbons. In summary, we localized in detail 3 mGluR types at IHC ribbon synapses, providing a fundament for new therapeutical strategies that could protect the cochlea against noxious stimuli and excitotoxicity.-Klotz, L., Wendler, O., Frischknecht, R., Shigemoto, R., Schulze, H., Enz, R. Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses.
CRIS-Team Scopus Importer:2019-12-17
Keywords: cochlea; IHC; mGlu receptor; mGluR

Metabotropic glutamate receptors and interacting proteins: evolving drug targets - Enz, Ralf (Current Drug Targets, 2012)
The correct targeting, localization, regulation and signaling of metabotropic glutamate receptors (mGluRs) represent major mechanisms underlying the complex function of neuronal networks. These tasks are accomplished by the formation of synaptic signal complexes that integrate functionally related proteins such as neurotransmitter receptors, enzymes and scaffold proteins. By these means, proteins interacting with mGluRs are important regulators of glutamatergic neurotransmission. Most described mGluR interaction partners bind to the intracellular C-termini of the receptors. These domains are extensively spliced and phosphorylated, resulting in a high variability of binding surfaces offered to interacting proteins. Malfunction of mGluRs and associated proteins are linked to neurodegenerative and neuropsychiatric disorders including addiction, depression, epilepsy, schizophrenia, Alzheimer's, Huntington's and Parkinson's disease. MGluR associated signal complexes are dynamic structures that assemble and disassemble in response to the neuronal fate. This, in principle, allows therapeutic intervention, defining mGluRs and interacting proteins as promising drug targets. In the last years, several studies elucidated the geometry of mGluRs in contact with regulatory proteins, providing a solid fundament for the development of new therapeutic strategies. Here, I will give an overview of human disorders directly associated with mGluR malfunction, provide an up-to-date summary of mGluR interacting proteins and highlight recently described structures of mGluR domains in contact with binding partners.
EVALuna2:4679

Metabotropic glutamate receptors are differentially regulated under elevated intraocular pressure. - Dyka; May; Enz, Ralf (Journal of Neurochemistry, 2004)
Glaucoma is a leading cause of blindness, ultimatively resulting in the apoptotic death of retinal ganglion cells. However, molecular mechanisms involved in ganglion cell death are poorly understood. While the involvement of ionotropic glutamate receptors has been extensively studied, virtually nothing is known about its metabotropic counterparts. Here, we compared the retinal gene expression of metabotropic glutamate receptors (mGluR) in eyes with normal and elevated intraocular pressure (IOP) of DBA/2J mice, a model for secondary angle-closure glaucoma using RT-PCR and immunohistochemistry. Elevated IOP in DBA/2J mice significantly increased retinal gene expression of mGluR1a, mGluR2, mGluR4a, mGluR4b, mGluR6 and mGluR7a when compared to C57BL/6 control animals, while mGluR5a/b and mGluR8a were decreased and no difference was observed for mGluR3 and mGluR8b. Specific antibodies detected an increase of mGluR1a and mGluR5a/b in both synaptic layers and in the ganglion cell layer of the retina under elevated IOP. Because ganglion cell death in DBA/2J mice occurs most likely by apoptotic mechanisms, we demonstrated up-regulation of mGluRs in neurons undergoing apoptosis. In summary, we support the idea that the specific gene regulation of mGluRs is a part of the glaucoma-like pathological process that develops in the eyes of DBA/2J mice.
UnivIS-Import:2017-12-18:Pub.2004.med.IB.profes_1.metabo
Keywords: Apoptosis; Gene expression; Glaucoma; Immunocytochemistry; Retina; RT-PCR

Metabotropic Glutamate Receptors at Ribbon Synapses in the Retina and Cochlea - Klotz-Weigand, Lisa; Enz, Ralf (Cells, 2022)
Our senses define our view of the world. They allow us to adapt to environmental stimuli and are essential for communication and social behaviour. For most humans, seeing and hearing are central senses for their daily life. Our eyes and ears respond to an extraordinary broad range of stimuli covering about 12 log units of light intensity or acoustic power, respectively. The cellular basis is represented by sensory cells (photoreceptors in the retina and inner hair cells in the cochlea) that convert sensory inputs into electrical signals. Photoreceptors and inner hair cells have devel-oped a specific pre-synaptic structure, termed synaptic ribbon, that is decorated with numerous vesicles filled with the excitatory neurotransmitter glutamate. At these ribbon synapses, glutama-tergic signal transduction is guided by distinct sets of metabotropic glutamate receptors (mGluRs). MGluRs belong to group II and III of the receptor classification can inhibit neuronal activity, thus protecting neurons from overstimulation and subsequent degeneration. Consequently, dysfunction of mGluRs is associated with vision and hearing disorders. In this review, we introduce the principle characteristics of ribbon synapses and describe group II and III mGluRs in these fascinating structures in the retina and cochlea.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Bipolar cell; Cochlea; Dimerization; Inner hair cell; Metabotropic glutamate receptor; Photoreceptor; Protein interaction; Retina; Ribbon synapse; Short linear motif

MGluR7 is a presynaptic metabotropic glutamate receptor at ribbon synapses of inner hair cells - Klotz, Lisa; Enz, Ralf (The FASEB Journal, 2021)
Glutamate is the most pivotal excitatory neurotransmitter in the central nervous system. Metabotropic glutamate receptors (mGluRs) dimerize and can couple to inhibitory intracellular signal cascades, thereby protecting glutamatergic neurons from excessive excitation and cell death. MGluR7 is correlated with age-related hearing deficits and noise-induced hearing loss; however its exact localization in the cochlea is unknown. Here, we analyzed the expression and localization of mGluR7a and mGluR7b in mouse cochlear wholemounts in detail, using confocal microscopy and 3D reconstructions. We observed a presynaptic localization of mGluR7a at inner hair cells (IHCs), close to the synaptic ribbon. To detect mGluR7b, newly generated antibodies were characterized and showed co-localization with mGluR7a at IHC ribbon synapses. Compared to the number of synaptic ribbons, the numbers of mGluR7a and mGluR7b puncta were reduced at higher frequencies (48 to 64 kHz) and in older animals (6 and 12 months). Previously, we reported a presynaptic localization of mGluR4 and mGluR8b at this synapse type. This enables the possibility for the formation of homo- and/or heterodimeric receptors composed of mGluR4, mGluR7a, mGluR7b and mGluR8b at IHC ribbon synapses. These receptor complexes might represent new molecular targets suited for pharmacological concepts to protect the cochlea against noxious stimuli and excitotoxicity.
CRIS-Team Scopus Importer:2021-11-05
Keywords: cochlea; inner hair cell; metabotropic glutamate receptor; mGlu; ribbon synapse

PKCζ-interacting protein ZIP3 is generated by intronic polyadenylation, and is expressed in the brain and retina of the rat. - Urbanczyk, Andreas; Jünemann, Anselm; Enz, Ralf (Biochemical Journal, 2011)
Scaffold proteins contain multiple protein - protein interaction modules that physically assemble functionally related proteins into larger complexes. ZIPs [PKC (protein kinase C) ζ-interacting proteins] link the enzymatic activity of the atypical PKC isoforms PKCλ/ι or PKCζ to target proteins and are associated with neurodegenerative disorders. In the rat, alternative splicing generates three ZIP variants. Previously, we identified the ZIP3 transcript, containing 13 C-terminal amino acids encoded by intron 4, in the rat CNS (central nervous system). In the present study, we identified intronic polyadenylation signals in rat and hu man ZIP genes [known as SQSTM1 (sequestosome-1) in humans] and detected the corresponding ZIP3-like transcripts. In addition, we generated ZIP3-specific immune sera and observed expression of the protein in the brain and retina of the adult rat. In the retina, ZIP3 is present in nuclear layers where it co-localizes with PKCζ. An immune serum recognizing all three ZIP isoforms labelled the same cells as the newly generated ZIP3-specific antibodies and, in addition, stained both synaptic layers of the retina. There, ZIPs are localized in axon terminals of rod bipolar cells that also contain ZIP-interacting PKCζ and GABA C (γ-aminobutyric acid type C) receptors. In summary, we detected ZIP3-like transcripts in ratand human-derived samples and describe the expression of ZIP3 in the rat CNS. © The Authors Journal compilation © 2011 Biochemical Society.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.pkc950
Keywords: γ-aminobutyric acid type C (GABA; p62; Protein kinase Cζ-interacting protein 3 (ZIP3); Retina; Sequestosome-1 (SQSTM1)

PNUTS forms a trimeric protein complex with GABAC receptors and protein phosphatase 1. - Rose, Melanie; Dütting, Eva; Schröder, Nadja; Sticht, Heinrich; Brandstätter, Johann Helmut; Enz, Ralf (Molecular and Cellular Neuroscience, 2008)
Phosphorylation and dephosphorylation of neurotransmitter receptors represent an important mechanism to regulate synaptic signal transduction. Here, we identified PNUTS, a targeting subunit of protein phosphatase 1 (PP1) as a new binding partner of GABAC receptors. In the mammalian retina, PNUTS is co-expressed with GABAC receptors and PP1 in bipolar cells. PNUTS and PP1 were detected in membrane protein preparations of the retina and precipitate with GABAC receptor specific antibodies. Furthermore, PNUTS shuttles from the nucleus to the membrane in cells co-expressing GABAC receptors. We show simultaneous binding of PP1 and GABAC receptors to different domains of PNUTS, demonstrating that PNUTS cross-links PP1 and GABAC receptors. Finally, modeling studies showed that the PP1 docking motif of PNUTS fits into the binding pocket on the enzyme surface, despite a C-terminal adjacent proline. We suggest that PNUTS targets PP1 to synaptic sites, acting as a temporary bridge between the phosphatase and GABAC receptors. © 2007 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2008.med.IB.profes_1.pnutsf_1
Keywords: Docking motif; GABA receptor; PP1C; Protein interaction; Retina; rho subunit

RanBPM is expressed in synaptic layers of the mammalian retina and binds to metabotropic glutamate receptors. - Seebahn, Angela; Rose, Melanie; Enz, Ralf (FEBS letters, 2008)
In the central nervous system, synaptic signal transduction depends on the regulation of neurotransmitter receptors by interacting proteins. Here, we searched for proteins interacting with two metabotropic glutamate receptor type 8 isoforms (mGlu8a and mGlu8b) and identified RanBPM. RanBPM is expressed in several brain regions, including the retina. There, RanBPM is restricted to the inner plexiform layer where it co-localizes with the mGlu8b isoform and processes of cholinergic amacrine cells expressing mGlu2 receptors. RanBPM interacts with mGlu2 and other group II and group III receptors, except mGlu6. Our data suggest that RanBPM might be associated with mGlu receptors at synaptic sites. © 2008 Federation of European Biochemical Societies.
UnivIS-Import:2017-12-18:Pub.2008.med.IB.profes_1.ranbpm
Keywords: mGlu2; mGlu8b; Protein interaction; RanBP9; RanBPM; Retina

Rod photoreceptor ribbon synapses in DBA/2J mice show progressive age-related structural changes. - Fuchs, Michaela; Scholz, Michael; Sendelbeck, Anna; Atorf, Jenny; Schlegel, Christine Julie; Enz, Ralf; Brandstätter, Johann Helmut (PLoS ONE, 2012)
The DBA/2J mouse is a commonly used animal model in glaucoma research. The eyes of DBA/2J mice show severe age-related changes that finally lead to the degeneration of retinal ganglion cells and the optic nerve. Recent electroretinogram studies identified functional deficits, which suggest that also photoreceptor cells are involved in the pathological processes occurring in the DBA/2J mouse retina. In a comparative study, we examined anatomical and molecular changes in the retinae of DBA/2J and C57BL/6 control mice with light and electron microscopy and with PCR analyses. In the retina of the DBA/2J mouse, we found a thinning of the outer plexiform layer, the first synaptic layer in the transfer of visual signals, and age-dependent and progressive degenerative structural changes at rod photoreceptor ribbon synapses. The structural ribbon changes represent a photoreceptor synaptic phenotype that has not yet been described in this animal model of secondary angle-closure glaucoma. Furthermore, genes of the classical complement cascade were upregulated in the photoreceptor cells of aging DBA/2J mice, suggesting a putative link between ribbon synapse degradation and the innate immune system. © 2012 Fuchs et al.
UnivIS-Import:2015-04-14:Pub.2012.med.IB.profes_1.rodpho

Simiate and the focal adhesion kinase FAK1 cooperate in the regulation of dendritogenesis - Rama, Ramya; Derlig, Kristin; Vießmann, Nina; Gossmann, Roman; Oriold, Fabian; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Scientific Reports, 2022)
Despite the crucial importance of dendritogenesis for the correct functioning of neurons, the molecular mechanisms underlying neuronal arborisation are still not well understood. Current models suggest that distinct parts and phases of dendritic development are regulated by the expression of distinct transcription factors, that are able to target the cytoskeleton. Two proteins recently implicated in dendritogenesis are the Focal Adhesion Kinase FAK1 and the Actin-binding protein Simiate. Using heterologous expression systems as well as mouse brain extracts in combination with coprecipitation assays, we show that Simiate is able to associate with FAK1. Differential centrifugation experiments further revealed the interaction to be present in cytosolic as well as nuclear fractions. Inside the nucleus though, Simiate preferentially binds to a FAK1 isoform of 80 kDa, which has previously been shown to regulate transcription factor activity. Investigating the function of both proteins in primary hippocampal cultures, we further found that FAK1 and Simiate have distinct roles in dendritogenesis: While FAK1 increases dendrite length and number, Simiate preferentially enhances growth and branching. However, if being confined to the nucleus, Simiate selectively triggers primary dendrite formation, enhancing transcription activity at the same time. Since the effect on primary dendrites is specifically re-normalized by a co-expression of FAK1 and Simiate in the nucleus, the data implies that the two proteins interact to counterbalance each other in order to control dendrite formation. Looking at the role of the cytosolic interaction of FAK1 and Simiate, we found that neurotrophin induced dendritogenesis causes a striking colocalisation of FAK1 and Simiate in dendritic growth cones, which is not present otherwise, thus suggesting that the cytosolic interaction stimulates growth cone mediated dendritogenesis in response to certain external signals. Taken together, the data show that FAK1 and Simiate exert several and distinct actions during the different phases of dendritogenesis and that these actions are related to their subcellular localisation and their interaction.
CRIS-Team Scopus Importer:2022-07-15

Simiate is an Actin binding protein involved in filopodia dynamics and arborization of neurons - Derlig, Kristin; Ehrhardt, Toni; Giessi, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Frontiers in Cellular Neuroscience, 2014)
The Actin cytoskeleton constitutes the functional base for a multitude of cellular processes extending from motility and migration to cell mechanics and morphogenesis. The latter is particularly important to neuronal cells since the accurate functioning of the brain crucially depends on the correct arborization of neurons, a process that requires the formation of several dozens to hundreds of dendritic branches. Recently, a model was proposed where different transcription factors are detailed to distinct facets and phases of dendritogenesis and exert their function by acting on the Actin cytoskeleton, however, the proteins involved as well as the underlying molecular mechanisms are largely unknown. Here, we demonstrate that Simiate, a protein previously indicated to activate transcription, directly associates with both, G- and F-Actin and in doing so, affects Actin polymerization and Actin turnover in living cells. Imaging studies illustrate that Simiate particularly influences filopodia dynamics and specifically increases the branching of proximal, but not distal dendrites of developing neurons. The data suggests that Simiate functions as a direct molecular link between transcription regulation on one side, and dendritogenesis on the other, wherein Simiate serves to coordinate the development of proximal and distal dendrites by acting on the Actin cytoskeleton of filopodia and on transcription regulation, hence supporting the novel model.
EVALuna2:4699

Spartin recruits PKC-ζ via the PKC-ζ interacting proteins ZIP1 and ZIP3 to lipid droplets. - Urbanczyk, Andreas; Enz, Ralf (Journal of Neurochemistry, 2011)
Protein kinase C-ζ interacting proteins (ZIP1-3) recruit the enzymatic activity of the atypical protein kinase C isoforms PKC-λ/ι or PKC-ζ to target proteins. In this study, we searched for binding partners of ZIP3 in the CNS and identified spartin, a multifunctional protein that is mutated in spastic paraplegia type 20. In transfected cells, spartin was present on the surface of lipid droplets (LD), whereas ZIP proteins appeared in intracellular speckles. In the presence of spartin, ZIP1 and ZIP3 were translocated to spartin-positive LD. This translocation was mediated by amino acids 196-393 of spartin that interacted with an N-terminal region of ZIP proteins. Furthermore, ZIP proteins interacted simultaneously with spartin and PKC-ζ, resulting in an enrichment of PKC-ζ on spartin/ZIP-labelled LD. Without spartin, neither ZIP proteins nor PKC-ζ were detected on LD. Interestingly, the presence of the spartin/ZIP/PKC-ζ complex increased LD size. This effect was most pronounced upon incorporation of the ZIP3 isoform into the trimer. Finally, we co-localized spartin, ZIP proteins and PKC-ζ in axon terminals of neurons in the mammalian retina. In summary, we describe spartin as new binding partner of the ZIP/PKC-ζ dimer that recruits PKC-ζ to LD and show that the expressed ZIP isoform regulates LD size. © 2011 The Authors. Journal of Neurochemistry © 2011 International Society for Neurochemistry.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.sparti
Keywords: lipid droplets; p62; protein kinase C-ζ interacting protein; retina; sequestosome-1 (SQSTM1); SPG20

Special characteristics of the transcription and splicing machinery in photoreceptor cells of the mammalian retina - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Cell and Tissue Research, 2015)
Chromatin organization and the management of transcription and splicing are fundamental to the correct functioning of every cell but, in particular, for highly active cells such as photoreceptors, the sensory neurons of the retina. Rod photoreceptor cells of nocturnal animals have recently been shown to have an inverted chromatin architecture compared with rod photoreceptor cells of diurnal animals. The heterochromatin is concentrated in the center of the nucleus, whereas the genetically active euchromatin is positioned close to the nuclear membrane. This unique chromatin architecture suggests that the transcription and splicing machinery is also subject to specific adaptations in these cells. Recently, we described the protein Simiate, which is enriched in nuclear speckles and seems to be involved in transcription and splicing processes. Here, we examine the distribution of Simiate and nuclear speckles in neurons of mouse retinae. In retinal neurons of the inner nuclear and ganglion cell layer, Simiate is concentrated in a clustered pattern in the nuclear interior, whereas in rod and cone photoreceptor cells, Simiate is present at the nuclear periphery. Further staining with markers for the transcription and splicing machinery has confirmed the localization of nuclear speckle components at the periphery. Comparing the distribution of nuclear speckles in retinae of the nocturnal mouse with the diurnal degu, we found no differences in the arrangement of the transcription and splicing machinery in their photoreceptor cells, thus suggesting that the organization of these machineries is not related to the animal's lifestyle but rather represents a general characteristic of photoreceptor organization and function.
EVALuna2:4722

Structural analysis of the protein phosphatase 1 docking motif: Molecular description of the binding specificity identifies new ligands. - Meiselbach, Heike; Sticht, Heinrich; Enz, Ralf (Chemistry & Biology, 2006)
The interplay between kinases and phosphatases represents a fundamental regulatory mechanism in biological systems. Being less numerous than kinases, phosphatases increase their diversity by the acquisition of a variety of binding partners, thereby forming a large number of holoenzymes. Proteins interacting with protein phosphatase 1 (PP1) often bind via a so-called docking motif to regulate its enzymatic activity, substrate specificity, and subcellular localization. Here, we systematically determined structural elements that mediate the binding specificity of PP1 interacting proteins, and propose a refined consensus sequence for high-affinity PP1 ligands. Applying this pattern to database searches, we predicted and experimentally confirmed several previously unknown PP1 interactors. Thus, the suggested PP1 docking motif enables a highly specific prediction of PP1 binding partners, thereby facilitating the genome-wide identification of PP1 interactors.<br
UnivIS-Import:2015-04-14:Pub.2006.med.IB.profes_1.struct

Structural characterization of intracellular C-terminal domains of group III metabotropic glutamate receptors. - Seebahn, Angela; Dinkel, Holger; Mohrlüder, J.; Hartmann, Rainer; Vogel, N.; Becker, Cord-Michael; Sticht, Heinrich; Enz, Ralf (Febs Letters, 2011)
Metabotropic glutamate receptors (mGluRs) are regulated by interacting proteins that mostly bind to their intracellular C-termini. Here, we investigated if mGluR6, mGluR7a and mGluR8a C-termini form predefined binding surfaces or if they were rather unstructured. Limited tryptic digest of purified peptides argued against the formation of stable globular folds. Circular dichroism, 1H NMR and 1H 15N HSQC spectra indicated the absence of rigid secondary structure elements. Furthermore, we localized short linear binding motifs in the unstructured receptor domains. Our data provide evidence that protein interactions of the analyzed mGluR C-termini are mediated rather by short linear motifs than by preformed folds. © 2011 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.struct
Keywords: G-protein coupled receptor; Metabotropic glutamate receptor; Neurotransmitter receptor; Short linear motif

Structure of metabotropic glutamate receptor C-terminal domains in contact with interacting proteins - Enz, Ralf (Frontiers in Molecular Neuroscience, 2012)
Metabotropic glutamate receptors (mGluRs) regulate intracellular signal pathways that control several physiological tasks, including neuronal excitability, learning, and memory. This is achieved by the formation of synaptic signal complexes, in which mGluRs assemble with functionally related proteins such as enzymes, scaffolds, and cytoskeletal anchor proteins. Thus, mGluR associated proteins actively participate in the regulation of glutamatergic neurotransmission. Importantly, dysfunction of mGluRs and interacting proteins may lead to impaired signal transduction and finally result in neurological disorders, e.g., night blindness, addiction, epilepsy, schizophrenia, autism spectrum disorders and Parkinson's disease. In contrast to solved crystal structures of extracellular N-terminal domains of some mGluR types, only a few studies analyzed the conformation of intracellular receptor domains. Intracellular C-termini of most mGluR types are subject to alternative splicing and can be further modified by phosphorylation and SUMOylation. In this way, diverse interaction sites for intracellular proteins that bind to and regulate the glutamate receptors are generated. Indeed, most of the known mGluR binding partners interact with the receptors' C-terminal domains. Within the last years, different laboratories analyzed the structure of these domains and described the geometry of the contact surface between mGluR C-termini and interacting proteins. Here, I will review recent progress in the structure characterization of mGluR C-termini and provide an up-to-date summary of the geometry of these domains in contact with binding partners.
EVALuna2:4691

Studying protein function and the role of altered protein expression by antibody interference and three-dimensional reconstructions - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Journal of Visualized Experiments, 2016)
A strict management of protein expression is not only essential to every organism alive, but also an important strategy to investigate protein functions in cellular models. Therefore, recent research invented different tools to target protein expression in mammalian cell lines or even animal models, including RNA and antibody interference. While the first strategy has gathered much attention during the past two decades, peptides mediating a translocation of antibody cargos across cellular membranes and into cells, obtained much less interest. In this publication, we provide a detailed protocol how to utilize a peptide carrier named Chariot in human embryonic kidney cells as well as in primary hippocampal neurons to perform antibody interference experiments and further illustrate the application of three-dimensional reconstructions in analyzing protein function. Our findings suggest that Chariot is, probably due to its nuclear localization signal, particularly well-suited to target proteins residing in the soma and the nucleus. Remarkably, when applying Chariot to primary hippocampal cultures, the reagent turned out to be surprisingly well accepted by dissociated neurons.
EVALuna2:4743
Keywords: Active motif; Antibody interference; Bioengineering; Issue 110; Nuclear proteins; Primary hippocampal cultures; Protein expression; Three-dimensional reconstructions

Subunits of the epithelial sodium channel family are differentially expressed in the retina of mice with ocular hypertension. - Enz, Ralf; et al. (Journal of Neurochemistry, 2005)
Glaucoma is a prevalent cause of blindness, resulting in the apoptotic death of retinal ganglion cells and optic nerve degeneration. The disease is often associated with elevated intraocular pressure, however, molecular mechanisms involved in ganglion cell death are poorly understood. To identify proteins contributing to this pathological process, we analysed the retinal gene expression of DBA/2J mice that develop an elevated intraocular pressure by the age of 6 months with subsequent ganglion cell loss. In this study, we identified subunits of the epithelial sodium channel (ENaC) family that are specifically expressed under elevated intraocular pressure. Using reverse transcriptase polymerase chain reaction we observed a significant increase of α-ENaC in the neuronal retina of DBA/2J mice when compared with control animals, while β-ENaC and γ-ENaC were not detectable in this tissue. Specific immune sera to ENaC subunits showed up-regulation of α-ENaC in synaptic and nuclear layers of the retina, and in the retinal pigment epithelium. Consistent with our polymerase chain reaction data, β-ENaC was not detected by specific antibodies in the retina, while γ-ENaC was only present in the retinal pigment epithelium under ocular hypertension. Finally, the increase of α-ENaC gene expression in the neuronal retina and the retinal pigment epithelium was not observed in other tissues of DBA/2J mice. Since the intraocular pressure is regulated by the transport of aqueous humour across epithelial structures of the eye that in turn is associated with ion flux, the specific up-regulation of ENaC proteins could serve as a protecting mechanism against elevated intraocular pressure. © 2005 International Society for Neurochemistry.
UnivIS-Import:2017-12-18:Pub.2005.med.IB.profes_1.subuni
Keywords: ENaC; Gene expression; Glaucoma; Intraocular pressure; Retina

Sumo E3 ligases are expressed in the retina and regulate sumoylation of the metabotropic glutamate receptor 8b. - Duetting, Eva; Schroeder-Kress, Nadja; Sticht, Heinrich; Enz, Ralf (Biochemical Journal, 2011)
The central nervous system regulates neuronal excitability by macromolecular signalling complexes that consist of functionally related proteins, including neurotransmitter receptors, enzymes and scaffolds. The composition of these signal complexes is regulated by post-translational modifications, such as phosphorylation and SUMOylation (SUMO is small ubiquitin-related modifier). In the present study, we searched for proteins interacting with the intracellular C-termini of the metabotropic glutamate receptors mGluR8a and mGluR8b and identified proteins of the SUMOylation and NEDDylation machinery. The SUMO E3 ligases Pias1 [Pias is protein inhibitor of activated STAT (signal transducer and activator of transcription)] and Pias3L interacted strongly with mGluR8b, and were co-localized with the E2-conjugating Ubc9, SUMO1 and mGluR8b in cell bodies present in the ganglion cell layer of the mammalian retina. SUMO1 conjugation of Lys 882, present in a bona fide consensus sequence for SUMOylation (VKSE) in the mGluR8b C-terminus, was enhanced by addition of Pias1, consistent with an interaction between both proteins. Mutation of Lys 882 to arginine reduced, but did not abolish, mGluR8b SUMOylation. Co-mutating a second lysine residue (Lys 903) located in the mGluR8b isoform-specific C-terminus largely prevented SUMO1 conjugation by Ubc9. Modelling studies suggested that Lys 903 contacts Ubc9 and thus is part of the non-canonical SUMOylation site VKSG. In summary, the results of the present study show in vivo SUMOylation of the complete mGluR8b and co-localize proteins of the SUMOylation machinery in the retina. © The Authors Journal compilation © 2011 Biochemical Society.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.sumoe3
Keywords: G-protein-coupled receptor (GPCR); Metabotropic glutamate receptor (mGluR); Protein inhibitor of activated STAT (signal transducer and activator of transcription) 1 (Pias1); Retina

The actin-binding protein Filamin-A interacts with the metabotropic glutamate receptor type 7. - Enz, Ralf (FEBS letters, 2002)
A yeast two-hybrid screen identified Filamin-A as a binding partner of the metabotropic glutamate receptor type 7b (mGluR7b) splice variant. In addition, Filamin-A interacted with mGluR4a, mGluR5a, mGluR5b, mGluR7a and mGluR8a. Domain mapping revealed that alternative splicing of mGluR4, mGluR7 and mGluR8 C-termini regulated the interaction. A conserved tyrosine within mGluR C-termini was identified to mediate the binding to Filamin-A. Protein interactions were verified in biochemical assays using recombinant and native proteins. Finally, co-expression of Filamin-A and mGluR7 splice variants was shown in brain regions. These findings suggest that Filamin-A may physically link metabotropic glutamate receptors to the actin cytoskeleton. © 2002 Federation of European Biochemical Societies. Published by Elsevier Science B.V. All rights reserved.
UnivIS-Import:2017-12-18:Pub.2002.med.IB.profes_1.theact
Keywords: Expression pattern; Filamin-A; mGluR; Protein-protein interaction; Yeast two-hybrid

The metabotropic glutamate receptor mGluR7b binds to the catalytic -subunit of protein phosphatase 1. - Enz, Ralf (Journal of Neurochemistry, 2002)
Correct targeting of enzymes represents an important biological mechanism to control post-translational modifications of neurotransmitter receptors. The metabotropic glutamate receptor type 7 (mGluR7) exists in two splice variants (mGluR7a and mGluR7b), defined by different C-termini that are phosphorylated by protein kinase C (PKC). Recently, the search for mGluR7a binding partners yielded several proteins that interacted with its C-terminus. Here, a yeast two-hybrid screen using the mGluR7b C-terminus identified both variants of the catalytic γ-subunit of protein phosphatase 1 (PP1γ1 and PP1γ2) as binding partners. The minimal interacting region of PP1γ1/2 contained the core domain and was homologous to a region of PP1α that is needed for functional expression. Although this core domain is highly conserved within the protein phosphatase family, PP1α1 and PP1β did not interact with mGluR7b. Binding between PP1γ1 and mGluR7b might be regulated by alternative splicing, as the variant-specific distal part of the mGluR7b C-terminus mediated the interaction. Within this domain, amino acids involved in the binding to PP1γ1 were mapped and biochemical assays using recombinant and native proteins verified the proposed interaction. Finally, the expression pattern of PP1γ1, PP1γ2 and mGluR7b was analysed in various CNS regions. In summary, these results suggest a regulation of mGluR7b by PP1γ.
UnivIS-Import:2017-12-18:Pub.2002.med.IB.profes_1.themet
Keywords: Expression pattern; G-protein coupled receptor; PP1γ1; PP1γ2; Protein interaction

The TAX1 binding protein 1 is expressed in the retina and interacts with the GABAC receptor rho1 subunit. - Ulrich, Melanie; Seeber, Silke; Becker, Cord-Michael; Enz, Ralf (Biochemical Journal, 2007)
UnivIS-Import:2015-04-14:Pub.2007.med.IB.profes_1.thetax

The trick of the tail: protein-protein interactions of metabotropic glutamate receptors. - Enz, Ralf (Bioessays, 2007)
It was initially believed that G-protein-coupled receptors, such as metabotropic glutamate receptors, could simply be described as individual proteins that are associated with intracellular signal cascades via G-proteins. This view is no longer tenable. Today we know that metabotropic glutamate receptors (mGluRs) can dimerize and bind to a variety of proteins in addition to trimeric G-proteins. These newly identified protein interactions led to the discovery of new regulatory mechanisms that are independent of and sometimes synergistic with the classical G-protein-coupled second messenger pathways. Notably, several of these mechanisms connect mGluR-mediated signaling to other receptor classes, thereby creating a network of different receptor types and associated signal cascades. The intracellular C-termini of mGluRs play a key role in the regulation of these networks, and various new protein interactions of these domains were described recently. Because mGluRs are involved in a variety of physiological and pathophysiological processes, some of the proteins interacting with this receptor class have potential as valuable pharmaceutical targets. This review will give a comprehensive overview of proteins interacting with mGluR C-termini, highlight new evolving regulatory mechanisms for glutamatergic signal transduction and discuss possibilities for future drug development. © 2006 Wiley Periodicals, Inc.
UnivIS-Import:2017-12-18:Pub.2007.med.IB.profes_1.thetri

ZIP3, a New Splice Variant of the PKC-ζ-interacting Protein Family, Binds to GABAC Receptors, PKC-ζ, and Kvβ2 - Croci, Cristina; Brandstätter, Johann Helmut; Enz, Ralf (Journal of Biological Chemistry, 2003)
The correct targeting of modifying enzymes to ion channels and neurotransmitter receptors represents an important biological mechanism to control neuronal excitability. The recent cloning of protein kinase C-zeta interacting proteins (ZIP1, ZIP2) identified new scaffolds linking the atypical protein kinase PKC-ζ to target proteins. GABAC receptors are composed of three ρ subunits (ρ1-3) that are highly expressed in the retina, where they are clustered at synaptic terminals of bipolar cells. A yeast two-hybrid screen for the GABAC receptor ρ3 subunit identified ZIP3, a new C-terminal splice variant of the ZIP protein family. ZIP3 was ubiquitously expressed in non-neuronal and neuronal tissues, including the retina. The ρ3-binding region of ZIP3 contained a ZZ-zinc finger domain, which interacted with 10 amino acids conserved in ρ1-3 but not in GABAA receptors. Consistently, only ρ1-3 subunits bound to ZIP3. ZIP3 formed dimers with ZIP1-3 and interacted with PKC-ζ and the shaker-type potassium channel subunit Kvβ2. Different domains of ZIP3 interacted with PKC-ζ and the p3 subunit, and simultaneous assembly of ZIP3, PKC-ζ and ρ3 was demonstrated in vitro. Subcellular co-expression of ZIP3 binding partners in the retina supported the proposed protein interactions. Our results indicate the formation of a ternary postsynaptic complex containing PKC-ζ, ZIP3, and GABAC receptors.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.profes_1.zip3an